The science of ADHD : a guide for parents and professionals - Chandler, Chris, 1966- (Chichester, UK : Wiley-Blackwell, 2010)
'Attention-Deficit Hyperactivity Disorder is a long-term disorder affecting many children and adults. It is also a highly controversial psychiatric disorder; in its cause, its diagnosis, and the effect of diagnosis on the patient. This controversy is exacerbated by the commonly recommended treatment for the condition - Ritalin. The Science of ADHD addresses the scientific status of ADHD in an informed and accessible way, without recourse to emotional or biased viewpoints. The very latest studies are used to present a reasoned account of ADHD and its treatment. The Science of ADHD is highly multidisciplinary, covering the areas of genetics, neuroscience, psychology and treatment. The ever increasing scientific evidence is described and discussed, informing the reader of the limitations of the science, but also the benefits that scientific enquiry can bring to understanding what goes on in the ADHD brain'--
Includes bibliographical references and index.
Keywords: Attention-deficit hyperactivity disorder